A new modulator for digital RF power amplifiers utilizing a wavetable approach. Issue 6 (7th August 2017) - Hühn, Florian; Wentzel, Andreas; Heinrich, Wolfgang
Abstract : This paper presents for the first time a wavetable-based coding scheme to generate a high-speed binary input signal for digital RF power amplifiers. The approach maximizes the utilization of the time domain handling capabilities of the pulse forming circuit. Key features are a greatly improved output spectrum purity in comparison with common digital modulators, the ability to adjust the modulator to any given pulse forming hardware and a built-in signal correction option that comes without additional computational cost. To give a first impression on the modulators behavior and its possibilities to adapt to different hardware constraints, simulations are carried out for different parameter variations and for different baseband bandwidths. Furthermore, the proposed concept is emulated with an arbitrary waveform generator to gather additional measurement data. For a 5 MHz wideband code division multiple access (WCDMA) signal (6.5 dB peak-to-average power ratio) at 900 MHz, an error vector magnitude (EVM) of 0.26% and better than >58 dB adjacent channel leakage ratio (ACLR) were recorded. To the authors' knowledge, these are the best values achieved so far for a single-bit coding scheme without digital predistortion that still maintains maximum power coding efficiency.